Implementation of a Web-Based Alumni Information System as a Digital Strategy in Graduate Tracking (Tracer Study) at SMKN 6 Mataram - Harmaen Harmaen; Triya Rezeki Umais; Mohammad Mustari (Indonesian Journal of Educational Innovation, 2025)
The implementation of a web-based alum information system is a digital strategy for tracking graduates of SMKN 6 Mataram. This study aims to understand the implementation process, the effectiveness of the system, and the contribution of graduate tracking in improving the quality of vocational education. The method employed is a qualitative case study at SMKN 6 Mataram. Data collection in this study uses observation, documentation, and interviews. The data analysis employed in this study is based on Miles and Huberman's theory, which involves the stages of data reduction, data presentation, and conclusion drawing. The findings of this study confirm SMKN 6 Mataram's commitment to integrating information technology into education management. Tracer studies or graduate tracking are efforts to provide an accurate and up-to-date database for the school's strategic policy foundation. This implementation occurs through four main stages: planning and design, development and testing, socialisation and full implementation, and monitoring and evaluation. There are also challenges faced in implementing the alum information system, such as low active participation of alums, technical constraints, resources, and uneven digital culture.